Flexible electrostatic transducer array with displacement control for haptic sensing and actuation - Trase, Ian; Tan, Hong Z.; Chen, Zi; Zhang, John X.J. (Sensors and actuators. A. Physical., 2021)
[Display omitted] •Accurate load sensing shown for flexible electrostatic transducer.•Demonstration of simultaneous sensing and actuation for the transducer.•Development of automatic displacement control for the transducer. We developed flexible electrostatic transducers with both a single element and a 2 × 2 array format to actuate at a precise displacement across a range of loads with a control circuitry and algorithm. The transducer, composed of a moving buckled film with an integrated electrode and a rigid electrode, can be used to simultaneously generate and sense displacements. A circuit and computer program were designed to demonstrate displacement control and quantify the sensing precision of the transducer. Specifically, we applied a range of voltage and load conditions to the transducer and array and measured the displacement while under loading through capacitive sensing. The change in capacitance was linear with respect to the area of the electrode in contact and matched theoretical predictions when described as a function of the displacement. The transducer was loaded with weights in the range of 5–27 mN and capacitance-driving voltage graphs were obtained. An 8 Hz driving frequency was used to move the transducer, while a 10.8 kHz signal was used to sense the capacitance. These were used to build a predictive model to correct for sensed load to maintain a average displacement. It was found that a transducer of dimensions 10 mm X 40 mm was able to maintain displacement under loads of 5–27 mN, while a matrix composed of 10 mm X 20 mm transducers was able to maintain displacement under loads of 2.5−11 mN. In general, the detection thresholds of human skin can range between 5–20 mN of force and 2–20 u m of displacement for frequencies between 1 Hz and 250 Hz, so these values are in line with what is needed to build a functional haptic wearable device. The present work provides a method to quantitatively measure and control a new type of flexible transducer for a variety of haptic applications.